2021
DOI: 10.32939/ijcd.v3i2.1021
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kontrol Diri Siswa Saat Belajar dari Rumah dalam Menggunakan Handphone pada Masa Pandemi COVID-19

Abstract: This research is motivated by indications that students have not been able to control themselves in the use of mobile phones, so it can negatively affect students. This study aims to analyze students' self-control when learning from home in using mobile phones during the Covid-19 outbreak. This study is a type of descriptive quantitative research with a research population of all students of State Junior High School 3 Sungai Penuh numbering 149 people, then the sample of this study was taken with total samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…Selfcontrol becomes the dominating component during the pandemic and lockdown compared to self-regulation [9]. Within self-control, there is the ability to read or assess one's own situation and environment, manage and adapt to the environment, and express oneself during social interactions [19]. Therefore, self-control involves efforts to organize, guide, manage, and direct behavior towards positive consequences [18], [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selfcontrol becomes the dominating component during the pandemic and lockdown compared to self-regulation [9]. Within self-control, there is the ability to read or assess one's own situation and environment, manage and adapt to the environment, and express oneself during social interactions [19]. Therefore, self-control involves efforts to organize, guide, manage, and direct behavior towards positive consequences [18], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Research on self-control relevant to the aforementioned definition and concept has been extensively discussed in several studies, both prior to and during the pandemic. Hendra et al's study categorized the self-control abilities of students using smartphones for learning during the pandemic as moderate [19], while Sari et al [23] classified them as high. Juliawati, Yandri, and Afrifadela [24] found that students' selfcontrol fell within the category of fairly good, while Damayanti and Ilyas [25] reported that students' self-control was good.…”
Section: Introductionmentioning
confidence: 99%
“…Cyberbullying terjadi karena adanya suatu kebiasaan dan lingkungan. Kebiasaan anak remaja atau peserta didik dalam menggunakan internet terutama sosial media sudah menjadi suatu ketagihan untuk memenuhi kebutuhan sehari -hari mereka (Hendra et al, 2021).…”
unclassified